Perancangan Sistem Informasi Penerimaan Karyawan Berbasis Web pada PT. Meerkats Flexipack Indonesia - Jacko Pastorius; Jay Idoan Sihotang (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2018)
Advances in Information and Communications Technology these days have been growing fastly, and Web-based application software is one of its obvious examples. Based on this fact, this study aims to (1) assist PT. Meerkats Flexipack Indonesia in presenting a job vacancy information and processing applicants data on database so the HRD division can easily find the right applicant data, (2) facilitate prospective employees in getting a job vacancy information and apply a job without come directly to the company. By using the System Development Life Cycle (SDLC) method such as Waterfall model which includes the stages of planning, analysis, design and implementation of the system. The results achieved from this research is a web-based acceptance information system. With the implementation of this system, companies can easily provide a job vacancy information and choose the applicants who want and applicants who will apply for jobs can also easily access and provide information without having to come directly to the company. In addition, the use of this system can reduce the pile of paper files that can take up space.